1991
DOI: 10.3109/00016359109005924
|View full text |Cite
|
Sign up to set email alerts
|

Influence of delmopinol on bacterial ζ-potentials and on the colloidal stability of bacterial suspensions

Abstract: Delmopinol is a low molecular weight surface-active compound that has been shown to be effective against dental plaque both in vitro and in vivo and against gingivitis in vivo. To study the mode of action of delmopinol, the influence of the compound on the stability of bacterial suspensions, both with and without saliva, and on the zeta-potentials of oral streptococci was studied. The results showed that delmopinol reduced the magnitude of the zeta-potentials, but, in contrast, the colloidal stability of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This finding is similar to the colloidal study that examined the influence of a cationic detergent on the stability of bacterial suspensions 23) . These findings strongly suggested that, because the chitosan used in this study carried positive charges, it functioned as a polycationic agent by adsorbing onto cell surfaces and by bridging together into aggregates to prevent adsorption of bacteria onto S-HA.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is similar to the colloidal study that examined the influence of a cationic detergent on the stability of bacterial suspensions 23) . These findings strongly suggested that, because the chitosan used in this study carried positive charges, it functioned as a polycationic agent by adsorbing onto cell surfaces and by bridging together into aggregates to prevent adsorption of bacteria onto S-HA.…”
Section: Discussionsupporting
confidence: 84%
“…Although delmopinol apparently lacks a substantial antimicrobial effect, it has an effect on plaque and gingivitis (8). It has been suggested that delmopinol reduces the cohesive forces within dental plaque (29). It is probable that its physicochetnical properties play a significant role in its effect as a plaquecontrol agent (5).…”
Section: Supragingivai Piaque Compositionmentioning
confidence: 99%
“…Delmopinol is a tertiary amine surfactant, developed as an anti-plaque agent to reduce plaque and gingivitis as an adjunct to normal mechanical cleaning where this has proved inadequate. In opposite to some other anti-plaque chemicals, including chlorhexidine, which owe their effectiveness to a combination of bacteriostatic and bactericidal activity, delmopinol was developed to have comparably low antimicrobial properties, and by interfering with plaque matrix formation promote a microbial flora compatible with dental health [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%